Accumulation and potential analysis of self-sourced natural gas in the Ordovician Majiagou Formation of Ordos Basin, NW China - Wei LI; Jianqi TU; Jing ZHANG; Bin ZHANG (Petroleum Exploration and Development, 2017)
The characteristics of the marine carbonate source rocks and the accumulation and potential of self-sourced natural gas in the Ordovician Majiagou Formation of the Ordos Basin are investigated based on recent exploration by using geochemistry and gas-source correlation methods. Massive source rocks are developed around the salt depression, east of the paleo-uplift in the Ordovician Majiagou Formation during the Caledonian; and the natural gases produced by argillaceous dolomite and dolomitic mudstone are the major contributors of the Ordovician gas field. Besides widespread carbonate weathering crust reservoir, internal grain band dolomite reservoir are also well-developed in the Majiagou Formation, and both can act as favorable reservoirs. The natural gas of the Majiagou Formation is mainly self-sourced oil-type gas generated by in-situ source rock and accumulated near the source area. There is only limited local accumulation of natural gas produced in the upper strata and stored below. The Majiagou Formation around the salt depression has favorable conditions for large scale natural gas generation and accumulation, and has the advantage of collecting large area natural gas of self-generation and self-preservation. The frontier depression areas of the paleo-uplift to the west, north and south of Jingbian gas field are the potential Ordovician exploration targets in the future. Key words: Ordos Basin, Ordovician, Majiagou Formation, source rock, oil-type gas, natural gas accumulation, natural gas carbon isotope, natural gas resource